Positive influence of peers' interpersonal character on children's interpersonal character: The moderating role of children's and peers' social status. (February 2020) - Liu, Lisha; Xu, Liangyuan; Xiao, Xue; Liu, Lu; Li, Yanfang
Abstract: Introduction: Peers are an important source of influence on children's social development. This study investigated the positive association between peers' and children's interpersonal character (i.e., humanity and justice) and the moderating role of children's and peers' social status including wealth (family SES), power (class leadership), and prestige (social preference and social visibility). Methods: The participants were 1555 fourth-to ninth-graders ( M age = 12.76; 46.9% boys) and their reciprocal playmates in China. Questionnaires and peer nomination methods were used to measure interpersonal character and social status. Children's reciprocal playmates were used as the source of peer influence. Results: The playmates' humanity and justice were positively associated with the children's humanity and justice regardless of the child's grade, gender, or sibling status. Children's level of social visibility moderated the associations between the playmates' and the children's humanity and justice, with children of low social visibility being more strongly influenced by their playmates. The moderating role of playmates' social status was displayed in two modes and appeared in the secondary school and singleton samples. First, playmates with a higher social preference were more closely related to secondary school children's justice; second, playmates with lower social visibility were more closely related to secondary school children's and singletons' justice. Conclusions: The findings confirm the positive relationships between peers' and children's interpersonal character and reveal an important moderating role of prestige status, especially social visibility, among the relationships. This study extends the research on positive peer influence and contributes to knowledge of peer influence mechanisms.